Gene Mutation Annotation and Pedigree for Pulmonary Arterial Hypertension Patients in Han Chinese Patients - Mei-Tzu Wang; Ming-Ji Charng; Pei-Ling Chi; Chin-Chang Cheng; Cheng Chung Hung; Wei-Chun Huang (Ubiquity Press, 2021)
Background: The etiology of pulmonary arterial hypertension (PAH) in the Han Chinese population is poorly understood. Objectives: The aim of this study was to assess gene variants and associated functional annotations for PAH in Han Chinese patients. Methods: This is an ethnicity-based multi-centre study. Blood samples were collected from 20 PAH patients who volunteered for the study, and genetic tests were performed. The DAVID database was used to functionally annotate the genes 'BMPR2, ALK1, KCNK3, CAV1', and 'ENG'. Associated diseases, functional categories, gene ontology, and protein interactions were analysed using the Functional Annotation Tool in the DAVID database. GEO and ClinVar databases were also used for further comparison with gene mutations in our study. Results: PAH patient with gene mutations were female predominant except for a single male with a 'BMPR2' mutation. Locus variants in our study included 'G410DfsX1' in BMPR2, 'ex7 L300P,' 'ex4 S110PfsX40,' and 'ex7 E295Afs96X' in 'ALK1', 'c.-2C>A (IVS1-2 C>A)' in 'CAV1', and 'ex8 D366H' in ENG were not found in the ClinVar database associated with PAH. In addition to BMP and TGF-β pathways, gene ontology of input genes in the DAVID database also included pathways associated with nitric oxide signaling and regulation. Conclusions: This Multi-centre study indicated that 'G410DfsX1' in BMPR2, 'ex7 L300P,' 'ex4 S110PfsX40,' 'ex7 E295Afs96X' in 'ALK1', 'c.-2C>A (IVS1-2 C>A)' in 'CAV1', and 'ex8 D366H' in ENG were identified in Han Chinese patients with PAH. Females were more susceptible to PAH, and a relatively young age distribution was observed for patients with 'BMPR2' mutations.